THE EFFECT OF APPLYING BRAINSTORMING TECHNIQUE ON THE STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE PARAGRAPH - Mirna Fransisca; Zainuddin Zainuddin (Universitas Negeri Medan, 2012)
ABSTRACT This study aims at investigating the effect of applying Brainstorming Technique on the students’ achievement in writing descriptive paragraph. The population of this study was the Grade 8 students of of SMP Negeri 3 Aek Kuo, Labuhan Batu Utara. There were 8 classes which contained around 240 students. 2 classes out of eight classes were randomly taken as the sample of the research. The sample was divided into two groups. The first group (30 students) as the experimental group, while the rest (30 students) as the control group. The experimental group was taught by applying Brainstorming Technique., and the Control Group was taught by using Conventional Technique. The instrument for collecting the data was essay test. To obtain the reliability of the test, the writer used the inter-rater formula. The result of the study showed that the reliability of the test was 0.55. The data were analyzed by using t-test formula. The analysis showed that the scores of the students of the experimental group were significantly higher than the scores of the students in the control group at the level significance 0.5 with the degree of freedom (df) 58 the is 4,650. while the is 1,671. Therefore, the hypothesis is accepted. It means that that Brainstorming Technique significantly affects the students’ achievement in writing descriptive paragraph. Key words: Brainstorming, Writing, Descriptive Paragraph